An Analysis of Cultural Contents in EFL Textbook: “Bahasa Inggris untuk SMP/MTs Kelas VII” - Muhammad Qozoli Wahid; Imam Qalyubi; Zaitun Qamariah (Departement of Mathematics Education, 2023)
EFL textbooks are optimal resources for EFL teachers and students, providing essential materials for teaching and learning English. Cultural content in these textbooks is an important aspect that needs attention, because it plays an important role in shaping EFL students' attitudes and beliefs towards other cultures, especially in MTsN 1 school in Palangka Raya city. This study aims to find out (1) what aspects are included in the cultural content presented in the